Advances in signal processing and intelligent recognition systems : 4th International Symposium SIRS 2018, Bangalore, India, September 19-22, 2018, Revised selected papers /: 4th International Symposium SIRS 2018, Bangalore, India, September 19-22, 2018, Revised selected papers. (2019) - Unknown
No abstract available